Rice Husk Ash Pozzolanicity Assessment by Resistivity Method - Riza, Fetra; Abdul Rahman, Ismail; Hadipramana, Josef (International Journal of Integrated Engineering, 2022)
Assessment of pozzolanic reactivity commonly based on direct and indirect method which mostly used electrical conductivity method. However these methods limited by long duration requirement or need to be done in the laboratory. By modified sand box test to measured the electrical resistivity of Rice Husk Ash (RHA) as pozzolan, this investigation trying to offer simpler method which can be done in situ. The RHA was heated in the oven with several temperatures varying from 100Â°C to 600Â°C and tested for its electrical resistivity by mixing it with laboratory grade lime. The value of electrical resistivity then compared with the value of the Luxan method by using the same materials. The results showed similar trend with electrical conductivity method. Hence new pozzolanicity classification was proposed in line with this new pozzolanicity assessment.